Planet statistika: Raba statističnih testov - Erčulj, Vanja; Šulc, Ajda (University of Maribor Press, 2024)
Planet Statistics: Use of Statistical Tests. Data analysis is a key part of the research design. The aim of quantitative research is to generalise findings from a sample to a population. This is made possible by inferential statistics. This textbook presents the basic steps of statistical reasoning. The process of hypothesis testing and the statistical tests that can be used to test hypotheses are provided. Some basic, widely used, statistical tests are presented. A practical example illustrates the use of an individual statistical test, both without a statistical program and using PSPP and/or SPSS. Examples of the use of statistical tests in research articles are also given. The textbook is intended for anyone who wants to understand and apply statistical reasoning in their research work.